2011
DOI: 10.1007/s10654-011-9621-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and metabolic influences of fetal smoke exposure

Abstract: Many epidemiological studies showed associations of low birth weight with cardiovascular disease, type 2 diabetes and obesity. The associations seem to be consistent and stronger among subjects with a postnatal catch up growth. It has been suggested that developmental changes in response to adverse fetal exposures might lead to changes in the fetal anatomy and physiology. These adaptations may be beneficial for short term, but may lead to common diseases in adulthood. Maternal smoking during pregnancy is one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 118 publications
5
50
0
3
Order By: Relevance
“…(3) The prevalence of obesity in children of mothers who smoked during pregnancy has also been reported. (3,30) In the present study, the mean smoking history was higher among older smokers than among younger smokers, which is most probably related to longer tobacco use among older individuals and, therefore, to a longer smoking history. A study conducted in Brazil showed similar results among men, and the frequency of heavy smoking (> 20 cigarettes/day) was twice as high in those aged 18-24 years and in those aged 55-64 years, declining thereafter.…”
mentioning
confidence: 44%
“…(3) The prevalence of obesity in children of mothers who smoked during pregnancy has also been reported. (3,30) In the present study, the mean smoking history was higher among older smokers than among younger smokers, which is most probably related to longer tobacco use among older individuals and, therefore, to a longer smoking history. A study conducted in Brazil showed similar results among men, and the frequency of heavy smoking (> 20 cigarettes/day) was twice as high in those aged 18-24 years and in those aged 55-64 years, declining thereafter.…”
mentioning
confidence: 44%
“…Clearly there is a great deal of interest in cigarette smoking and use of other tobacco and nicotine delivery products in pregnant smokers due to the substantial adverse short- and longer-term impacts on the developing fetus (Bakker & Jaddoe, 2011; Cnattingius, 2004; Dietz et al, 2010). There are also well-substantiated differences in the smoking of pregnant women compared to the general population that warrant caution against assuming that observations regarding the effects of tobacco and nicotine in one group can be readily generalized to the other.…”
Section: Introductionmentioning
confidence: 99%
“…cadmium and other toxic factors that have direct adverse effects and might affect placental function and the fetal supply line (8). Maternal smoking leads to restricted blood flow in the vascular beds of specific fetal organs (8).…”
mentioning
confidence: 99%
“…Maternal smoking leads to restricted blood flow in the vascular beds of specific fetal organs (8). Animal studies demonstrated adverse effects of high maternal nicotine levels on metabolic development (9).…”
mentioning
confidence: 99%